Use of gabapentin for neuropathic pain therapy: A view from perspective of evidence-based medicine - O. I. Butranova; S. K. Zyryanov (Фармация и фармакология (Пятигорск), 2024)
The aim of the study was to analyze the literature sources for pharmacodynamic and pharmacokinetic features of gabapentin, providing its use in patients with neuropathic pain, as well as a comparative evaluation of its efficacy and safety when used in different doses.Materials and methods. PubMed, Google Scholar, EMBASE, ResearchGate scientific information network and elibrary.ru databases were used as search resources. The keywords used for the search were “gabapentin”, “mechanism of action”, “gabapentin targets”, “gabapentin pharmacodynamics”, “pharmacokinetics”, “pharmacokinetic parameters”, “neuropathic pain”, and “randomized clinical trials”. The depth of the search was 26 years (from 1998 to 2024). This review resulted in 87 literature sources.Results. Neuropathic pain (NeP) is one of the most common types of chronic pain, characterized by a high prevalence among people of the working age. Effective pharmacotherapy aimed at eliminating the pain syndrome is a key tool for improving the quality of life and preserving the work capacity of patients. Heterogeneity of etiologic factors involved in the genesis of NeP indicates the need to use drugs the analgesic effect of which is based on weakening the transmission of pain impulses in the CNS. In clinical trials, gabapentin has demonstrated efficacy in reducing the severity of pain in patients with postherpetic NeP, painful diabetic neuropathy and many other conditions accompanied by NeP. The dose of gabapentin 300 mg/day is the initial dose in the therapy of NeP and requires a further slow titration depending on the patient’s response to therapy and tolerability of the drug, especially in elderly and senile patients, as well as in patients with an impaired renal function. According to the published data, the most pronounced analgesic effect is achieved in the patients against the background of the gabapentin administration at a dose of 3600 mg/day.Conclusion. Gabapentin is the drug of choice in the management of patients with NeP of different etiology and intensity. A satisfactory safety profile and pharmacodynamic effects make gabapentin possible, despite the long history of its use, to remain a relevant drug used by a wide range of physicians, specialties, for pharmacotherapy of NeP patients.